BACKORDER RAW MATERIAL INVENTORY CONTROL SYSTEM WITH LEAD TIME AND ORDERING COST REDUCTION: CASE STUDY PT ICI PAINTS INDONESIA - Amran, Tiena Gustina; Lesmono, Dinar Suryo (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
This research investigates the continuous review inventory model involving variable leadÂ time with partial backorders, where the amount is uncertain. PT ICI Paints Indonesia is one ofÂ chemical industries which produced paint. The main problems faced by company are often occurÂ stock out and also over stock of raw material replenishment, and the second case is raw materialÂ ordering lead time which canât be controlled and determined its extent so the company moreÂ depend on the supplier policy. The purpose of this research is to suggest the optimal raw materialÂ inventory system alternatives synchronized with the stock out characteristics and the condition canÂ be occurred. Besides, the backorder raw material inventory control can reduce lead time and rawÂ material ordering cost. After the calculation, the optimal solution of inventory models can beÂ obtained; those are with backorder condition which produced the annual inventory total costÂ amount of 15.069.845.628, 27 rupiahs; which mean it just effectively save inventory cost by 5, 81%Â for the company.